Roman Empire – structure and functioning of Education (Research, Society and Development, 2022)
Roman Law, one of the springs of Western civilization, consists of the complex of rules in force in Rome during the thirteen centuries of Roman history. It governed the constant modification in the structure of the Roman Empire, according to the evolution of culture and the political, economic and social changes that characterized it. The article intends to shed light on the structure and functioning of Roman education. To this end, qualitative research was adopted, with a systematic bibliographic review. It is concluded that the structure comprises the two traditional degrees of grammar and rhetoric, in the grammar course, the Latin and Greek languages and the precise notions for this purpose are taught, in the rhetoric course, the interpretation of historians and orators is taught, the rules and the eloquence exercises occupy a prominent place, moreover the Romans knew how to transmit the practice of the ideals of respect for individual rights and political freedom, of the cultivation of personal and collective morality, of social excellence which is called culture.